Enhancing wind turbine blade lamination with nano particles for lightning-resistant - Wahdain, S. S.; Amir Izzani, Mohamed; Mohd Herwan, Sulaiman; Ahmad Salihin, Samsudin; Prasetyo, Moh Toni (IEEE, 2024)
Nanoparticles have emerged as promising agents for mitigating lightning protection on insulation surfaces, offering potential benefits for wind turbine blade design. This research investigates the integration of carbon nanoparticles into epoxy composites and fiber-reinforced polymers. Experimental findings demonstrate the effectiveness of nanoparticle doping in suppressing surface charge accumulation and enhancing insulation properties, such as flashover voltage and partial discharge. Wind turbines, composed of insulating materials, accumulate electrostatic charges during operation, posing a risk of lightning attachment. However, addressing the discharge of these charges remains understudied. Incorporating nano-composite materials into wind turbine blades presents an opportunity to improve breakdown strength and reduce corona generation. This project aims to assess the impact of fiberglass epoxy Nanocomposite on reducing the risk of lightning strikes on wind turbine blades through Finite Element Method simulations. Carbon Nano Tubes are selected as fillers based on their electrical conductivity and integrated into the blade structure to analyze their effect on electric field strength. Initial simulations reveal significant reductions in electric field distribution upon carbon nanotube integration, highlighting the efficacy of nanoparticle integration in mitigating surface charge accumulation and improving the electrical properties of insulating materials for high-voltage applications such as wind energy generation.